Trends and future projections of alcohol-attributable hepatitis B burden in women of childbearing age (1990–2040): a global analysis - Li, Jiaxing; Hu, Qihui; Wang, Jixing; Huang, Zhenhao; Cai, Hongli; Liu, Chang; Li, Hao; Tao, Rui (Frontiers in Public Health, 2025)
IntroductionChronic hepatitis B virus (HBV) infection affects over 254 million people globally, with women of childbearing age (WCBA) facing dual risks of vertical transmission and alcohol-exacerbated disease progression. This study quantifies the alcohol-attributable burden of HBV among WCBA across 204 countries from 1990 to 2021 and projects trends to 2040.MethodsData on deaths and Disability-Adjusted Life Years (DALYs) were extracted from the Global Burden of Diseases (GBD) Study 2021. Joinpoint regression and decomposition analyses were used to assess historical trends, while Bayesian Age-Period-Cohort (BAPC) analysis predicted future trends.ResultsBetween 1990 and 2021, global deaths showed a significant increase to 1,551.98 (95% UI: 700.34 to 2,707.01), accompanied by a rise in DALYs reaching 80,616.03 (95% UI: 37,268.53 to 139,146.25). This growth trajectory was primarily driven by population expansion. While age-standardized death and DALY rates exhibited a declining trend overall, epidemiological analysis revealed a transient rebound in DALYs between 1999 and 2005. Current projections using BAPC modeling suggest continued challenges, with deaths and DALYs anticipated to rise by 2040 under current intervention patterns.ConclusionDespite declining age-standardized rates, population growth and alcohol exposure necessitate region-specific interventions. These findings underscore the urgent need for WHO alcohol control policies and HBV birth-dose vaccination in low-SDI regions, particularly sub-Saharan Africa and South Asia, to achieve 2030 elimination targets.